Edith Stein in Russia - Sztajn, Oksana (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
In this article a reception of Edith Stein’s philosophy in Russian academic, religious, artistic and medial discourses is presented. The author discusses scholarly elaborations devoted to Stein, her presence in media, libraries and on the Internet. Then, the author analyses the actual state of research, notably feministic and gender approaches, as well as the issue of corporeality, artistic works devoted to Stein and the contents of information services and websites.